A Focus on L Dwarfs with Trigonometric Parallaxes. (14th May 2018) - Wang, Y.; Smart, R. L.; Shao, Z.; Jones, H. R. A; Marocco, F.; Luo, A.; Burgasser, A.; Zhong, J.; Du, B.
Abstract: We report new parallax measurements for 10 L- and early T-type dwarfs, five of which have no previous published values, using observations over 3 years at the robotic Liverpool Telescope. The resulting parallaxes and proper motions have median errors of 2 mas and 1.5 mas/year, respectively. Their space motions indicate they are all Galactic disk members. We combined this sample with other objects with astrometry from the Liverpool Telescope and with the published literature astrometry to construct a sample of 260 L- and early T type dwarfs with measured parallaxes, designated the Astrometry Sample. We study the kinematics of the Astrometry Sample, and derived a solar motion of ( U, V, W )⊙ = (7.9 ± 1.7, 13.2 ± 1.2, 7.2 ± 1.0) km s −1, with respect to the local standard of rest, in agreement with the recent literature. We derive a kinematic age of 1.5–1.7 Gyr for the Astrometry Sample assuming the age increases monotonically with the total velocity for a given disk sample. This kinematic age is less than half of the literature values for which used the same methods and similar but different low-mass dwarf samples. We believe this difference arises for two reasons: (1) the sample is mainly composed of mid to late L dwarfs, which are expected to be relatively young, and (2) the requirement that objects have a measured parallax biases the sample to the brighter examples, which tend to be younger.